Kepercayaan Pamali dalam Konteks Tindakan Sosial: Studi Living Hadis di Desa Singarajan Kecamatan Pontang - Dhiya’ulhaq, Muhammad Faiq; Fauzan, Muhammad Nur; Alif, Muhammad; Muhsin, Masrukhin (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
The This study aims to understand and analyze the belief in Pamali in the social actions of the Pontang community in Singarajan Village. The approach used is qualitative research with social science methods where data is obtained through interviews with the Pontang community in Singarajan Village, research and documentation. The data collected consisted of primary and secondary data sources. The results showed that Pamali plays an important role in the life of the Singarajan Village community as a tradition passed down from generation to generation. These beliefs influence daily behavior as they are considered capable of preventing disasters and bringing good luck based on strong cultural, ancestral and spiritual beliefs. Examples of Pamali that are still followed, such as the prohibition of cutting nails at night, reflect the diversity of people's beliefs in the supernatural. Although education and socialization have been conducted to reduce blind adherence to Pamali, these beliefs remain difficult to eliminate because they are embedded in the culture of the Pontang community. Social factors, intercultural interactions, and religious perspectives also influence views on Pamali. This phenomenon, such as the prohibition of singing in front of the stove, illustrates the beliefs that are still strongly held by the community. Although it has positive effects, such as increasing caution and respect for ancestral culture, Pamali also has a negative side, namely restricting mindsets, limiting development, and hindering the progress of Pontang society in the era of modernization and globalization.